Honduras : 2018 Article IV Consultation. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
The IMF-supported program (2014-17) succeeded in reducing Honduras' macroeconomic imbalances. The next step is to adopt institutional reforms to entrench macroeconomic stability to put Honduras on a higher potential growth path.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet